HISTORIOGRAPHY OF THE PERSIAN CAMPAIGN OF PETER THE GREAT 1722-1723 AND ITS RESULTS (TO THE 300TH ANNIVERSARY) - Magaramov, Sarafetdin Arifovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article is devoted to the historiographic understanding of the problem of the Persian campaign of 1722–1723. Peter the Great and the stay of the Russian imperial army in the southwestern Caspian region in the first third of the 18th century. The work examines the process of the formation and evolution of the approaches of historians and historical thought on the problem for almost three centuries. Historiographic comprehension of the problem will make it possible to trace the dynamics of historical thought in the history of the Persian campaign, identify the most poorly developed aspects, show innovative assessments of authors of different historical eras, and update new plots. The relevance of this study is also due to the absence of a historiographical sketch even in the genre of an article on the history of the Persian campaign of Peter I. The pre-revolutionary historiography’s practice of studying the Persian campaign in the context of studying the wars of conquest of the Russian Empire in the Caucasus is analyzed. The works of military and civil historians of this period served a political purpose - to substantiate the advancement and establishment of the empire in the Caucasus region. The main attention was paid to the military-political side of the campaign, its foreign policy background. At the same time, the first special historical studies on the history of the campaign appeared, which are valuable historiographic sources. Many of them were written on the basis of handwritten documents from the personal archive of Peter I, some of which were later lost or became difficult to access. In the Soviet era, the study of various aspects of the campaign, associated with its prerequisites and reasons, the economic and economic development of the region, was significantly expanding, new documentary data were introduced into scientific circulation. Soviet historians adhered to the concept of the objectively progressive meaning of the annexation of the Caspian regions to the Russian Empire, regardless of whatever goals tsarism pursued. The Persian campaign of Peter I was assessed as the protection of the Caucasian peoples from the tyranny of Iran and Turkey. In the last two or three decades, in the study of the problem of the military-political campaign of 1722-1723. empire, there were significant successes associated with the development of new plots, using modern historical approaches, and the introduction into scientific circulation of a colossal fund of archival documents and narrative sources. At the same time, in the 1990s, there are attempts to revise the “Persian campaign”, to replace it with a new name - “Caspian campaign”, which has not been established outside the limits of regional Caucasian studies. At the present stage, researchers deepen and expand the existing scientific understanding of this problem by applying such scientific approaches as the history of everyday life, military-historical anthropology. In modern domestic historiography, there has been a tendency to study the historical memory of Dagestan society about the image of Peter I and to study the problem from the standpoint of the Russian-Persian-Ottoman borderland (frontier), which acted not only as a zone of conflict, resistance, but also the interaction of border communities and their elites.
Keywords: Peter the Great; Persian campaign of the 1722-1723; Nizovoy Corps; Western Caspian region; historiography